The Cambridge history of China : Vol. 12. Republican China 1912-1949 : pt. 1 - Fairbank, John K. (Cambridge [England] ; New York : Cambridge University Press, 1983)
International scholars and sinologists discuss culture, economic growth, social change, political processes, and foreign influences in China since the earliest pre-dynastic period.
Includes bibliographical references and indexes.
Keywords: China -- History